2012
DOI: 10.1017/s1463423612000199
|View full text |Cite
|
Sign up to set email alerts
|

Self-care in primary care: findings from a longitudinal comparison study

Abstract: Aim: To examine the effects of self-care training workshops for primary healthcare workers on frequently attending patients. Background: Interventions to promote selfcare in frequent users of primary care services have had mixed results. This paper reports an evaluation of a self-care initiative that aimed to develop a practice-based strategy to support self-care. Methods: A 12-month longitudinal-matched comparison study was carried out in seven intervention and four comparison practices. The intervention was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In these tasks, HCPs, similar to patients, had to adopt a range of ‘technical’ and non-technical devices and processes into clinical practice. Factors influencing HCPs’ adoption included evidence that the solution works [ 14 , 60 ], the solution’s alignment with goals of the organisation within which the HCP worked [ 37 , 42 , 68 , 75 ], the integration of the solution into existing systems and practices [ 31 , 32 , 44 , 60 , 68 ], adaptability of the solution to learning and incorporating change [ 14 , 33 , 42 , 51 , 60 , 68 ], transfer of decision-making power to patients and the effect of the solution on patient-doctor relationship [ 37 , 49 , 68 , 71 ], time and resource constraints [ 54 , 78 ], incentives and motivation to use the solution [ 14 , 71 ], how the solution is promoted to the organisation within which the HCP worked [ 14 , 51 , 71 , 75 ], HCPs’ appraisal of level of patient skill and interest in the solution [ 42 , 71 , 80 ] and adaptability of the solution to current roles and responsibilities [ 14 , 32 , 44 , 49 , 60 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In these tasks, HCPs, similar to patients, had to adopt a range of ‘technical’ and non-technical devices and processes into clinical practice. Factors influencing HCPs’ adoption included evidence that the solution works [ 14 , 60 ], the solution’s alignment with goals of the organisation within which the HCP worked [ 37 , 42 , 68 , 75 ], the integration of the solution into existing systems and practices [ 31 , 32 , 44 , 60 , 68 ], adaptability of the solution to learning and incorporating change [ 14 , 33 , 42 , 51 , 60 , 68 ], transfer of decision-making power to patients and the effect of the solution on patient-doctor relationship [ 37 , 49 , 68 , 71 ], time and resource constraints [ 54 , 78 ], incentives and motivation to use the solution [ 14 , 71 ], how the solution is promoted to the organisation within which the HCP worked [ 14 , 51 , 71 , 75 ], HCPs’ appraisal of level of patient skill and interest in the solution [ 42 , 71 , 80 ] and adaptability of the solution to current roles and responsibilities [ 14 , 32 , 44 , 49 , 60 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Along with Murray et al who described ‘implementers’ as a previously under-studied group [ 15 ], we also found that there is still very little literature on managers’ experiences. Factors affecting implementation included ability to deliver intended benefits of the solution, engaging effectively with business models, sustainable funding and resources, creating effective policies such as making adoption mandatory for HCPs, compatible commissions process across sectors and buy in senior leadership or active champions [ 14 , 33 , 47 , 54 , 78 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations